By Cramer's rule, the solution can be found as the ratio of determinants. The numerator is the matrix with the right-side constants replacing the coefficients of the variable of interest. The denominator is the matrix of coefficients.
![x=\displaystyle\frac{det\left[\begin{array}{cc}-26&-6\\13&2\end{array}\right]}{det\left[\begin{array}{cc}-2&-6\\5&2\end{array}\right]}=((-26)(2)-(13)(-6))/((-2)(2)-(5)(-6))\\\\=(26)/(26)=1\\\\y=\frac{det\left[\begin{array}{cc}-2&-26\\5&13\end{array}\right]}{26}=((-2)(13)-(5)(-26))/(26)\\\\=(104)/(26)=4](https://img.qammunity.org/2019/formulas/mathematics/college/2kmajmx0ysgsnd9kavl6xsjmdcget6m2wz.png)
The solution is ...
... B. (1, 4)